HALAL FOOD CULTURE IN INDONESIA: Faith, Knowledge, and Demand - Hanapia, Asep Yusup; Nasution, Fatimah Zahra; Adam, Asep Muhammad; Rakhmat, Anwar Taufik; Paturochman, Iwan Ridwan (MIQOT: Jurnal Ilmu-ilmu Keislaman, 2025)
Consumption constitutes a central aspect of daily life, in which individuals are required to evaluate the appropriateness of products, particularly in relation to ethical and religious considerations such as halal compliance. This study analyzes how literacy of halal products can strengthen or weaken the relationship between economic factors and consumer preferences for the demand for halal food products among the Nahdatul Ulama Muslimat, Tasikmalaya City, West Java administrators. We used a sample of 100 women registered in Nahdlatul Ulama organizations in Tasikmalaya. In this study, the average age of the sample is 49, with an average education of 11.45 years, or equivalent to senior high school. We conducted data analysis using the ordered probit method. Meanwhile, the ordered probit estimation results show that halal literacy predicts increased demand for halal products due to cognitive aspects in consumption decision-making. However, income and religious beliefs also influence demand. The study also shows a positive relationship between price and demand, contradicting the conventional law of supply and demand in microeconomics. The study has limitations, including insufficient consideration of socio-demographic variables and product specifications, necessitating further research to gain a comprehensive understanding.